2006
DOI: 10.1002/acp.1208
|View full text |Cite
|
Sign up to set email alerts
|

The effect of presentation medium of post‐event information: impact of co‐witness information

Abstract: To determine the effects of presentation medium and social influence on the misinformation effect, two experiments using the misinformation paradigm were conducted. The misinformation was presented via a videotaped conversation between two confederates. Three target items were created. In Experiment 1, participants were exposed to misinformation via videotape, and showed a misinformation effect for one of three targets. In Experiment 2, misinformation was given via a written transcript. Participants showed a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…During the second session, participants were confronted with their written accounts. We chose to present their accounts in this way as written statements play an important role in the legal system, while research has shown that people are more easily misled when post‐event information is presented in a written form (Itsukushima, Nishi, Maruyama, & Takahashi, 2006). We asked participants to check their testimony carefully.…”
Section: Methodsmentioning
confidence: 99%
“…During the second session, participants were confronted with their written accounts. We chose to present their accounts in this way as written statements play an important role in the legal system, while research has shown that people are more easily misled when post‐event information is presented in a written form (Itsukushima, Nishi, Maruyama, & Takahashi, 2006). We asked participants to check their testimony carefully.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments exploring the misinformation effect used various forms of the original, as well as post‐event materials (which in the experimental condition contain misinformation about the original event), and various types of the memory test (Zaragoza et al, ). Of particular interest for the present research is the form in which the post‐event information is introduced: a written narrative seemingly summarizing the original video clip (e.g., Frost, Ingraham, & Wilson, ), a narrative delivered via audio recording (e.g., Blank, ; Vornik, Sharman, & Garry, ), questions containing misleading presuppositions (e.g., Loftus et al, ), misleading pictures (e.g., Pezdek, ), or videos (e.g., Itsukushima, Nishi, Maruyama, & Takahashi, ). However, in the vast majority of research of this kind, misleading post‐event information was introduced impersonally (or indirectly, as Blank et al, , put it); that is, the participants were presented with some sort of material, usually written, and they had to familiarize themselves with it individually.…”
mentioning
confidence: 99%
“…Third, research has shown that memory is unreliable and highly context dependent [27][28][29][30]. The way in which a question is phrased has the capacity to alter answers and memories.…”
Section: Complexity Sciencementioning
confidence: 99%